Adaptation of the Last Planner System methodology for the planning and control of industrial engineering projects: a case study - Trajano, Lara Teixeira Maciel; César, Cristina Guimarães; Nunes, Felipe Alexandre de Souza Félix (Brazilian Journal of Production Engineering, 2025)
Context. The Last Planner System (LPS), originally developed for construction, has proved effective in reducing waste and increasing efficiency in project planning and control. This study examined the adaptation of LPS to industrial engineering projects. Objective. To assess LPS’s contribution to efficiency, productivity, and resource management in an engineering context. Method. Case study with two-time windows: February–April 2024 and April–July 2024. LPS routines were implemented, including look ahead meetings, and indicators such as Percentage of Package Completed (PPC) and document advancement across two baselines were monitored. Results. PPC fell within ranges considered acceptable for construction, indicating good performance of the adaptation during the engineering phase. Look ahead meetings brought forward 6 documents in baseline 1 and 36 in baseline 2, helping to reduce schedule deviations. Conclusion. Adapting LPS to the industrial engineering context proved promising. Ongoing adjustments and close monitoring are reinforced as essential to maximise the performance of future projects.